FAKTOR – FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN DAN DAMPAKNYA PADA FUTURE EARNING GROWTH PERUSAHAAN DI SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BEI PERIODE 2010-2014 - Ricky Setiawan; Werner Ria Murhadi; Bertha Silvia S. (CALYPTRA, 2017)
Abstract This study aimed to analyze the factors that influence the dividend policy and its impact on future earnings growth .Variabel used include size, leverage¸ lagged dividend policy, growth, and profitability. This study uses a quantitative approach to the analyze and use two stage least square as a model. This study used a sample of firm in the sector of consumer goods industry that distribute the minimum dividend 2 times on 2010-2014. The results showed that variable size, dividend payment of the previous period, and profitability has a positive and significant impact on dividend policy. While variable growth leverage and significant negative effect on dividend policy. For the second model variables proftability have a significant negative effect on the future earnings growth. While the variable leverage have significant negative effect on the future earnings growth. Other variables such as dividend policy, size, and growth have no significant effect on future earnings growth. Keyword: Dividend Policy, Future Earning Growth, Profitability, Firm Growth, Firm Size, Financial Leverage.